The genus nectria (hypocreaceae) in panama (1982)
Thirty-two species of Nectria, Calonectria and Thyronectria collectedin Panama were studied and are described from specimens deposited in the collections, of The New York Botanical Garden. A synoptic key to the species is presented and Sphaerostilbe mammiformis Chardon is transferred to Nectria.